2018
DOI: 10.1007/s10654-018-0460-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and sub-types of cardiovascular disease death causes in a general population cohort

Abstract: Physical activity is thought to be cardioprotective, but associations with different subtypes of cardiovascular disease (CVD) are poorly understood. We examined associations between physical activity and seven major CVD death causes. The sample comprised 65,093 adults (aged 58 ± 12 years, 45.4% men) followed up over mean [SD] 9.4 ± 4.5 years, recruited from The Health Survey for England and the Scottish Health Surveys. A CVD diagnosis was reported in 9.2% of the sample at baseline. Physical activity was self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 18 publications
1
34
0
1
Order By: Relevance
“…Six of the studies were from Europe and two were from the US and the duration of follow-up ranged from 6 to 26 years. One additional study from the United Kingdom reported on sudden cardiac death and arrhythmias combined and was included in a sensitivity analysis [32]. In addition, two studies on cardiorespiratory fitness were analyzed separately [22,23], and two studies on vigorous activity Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six of the studies were from Europe and two were from the US and the duration of follow-up ranged from 6 to 26 years. One additional study from the United Kingdom reported on sudden cardiac death and arrhythmias combined and was included in a sensitivity analysis [32]. In addition, two studies on cardiorespiratory fitness were analyzed separately [22,23], and two studies on vigorous activity Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A UK study which reported on sudden cardiac death and arrhythmias combined [32] was included with the eight other studies in a sensitivity analysis [9,12,[19][20][21]32] (n = 9 studies, 1263 events and 201,391 participants) and the summary RR was 0.51 (95% CI: 0.44-0.60, I 2 = 0%). Alternatively, using WHO recommendations for leisure-time physical activity categories from the study by Hamer et al [32], the summary RR was 0.52 (95% CI: 0.45-0.60, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PASBAQ data is used to monitor adherence to UK PA recommendations [17,18] and for other epidemiological research [20,21]. The PASBAQ has demonstrated moderate-weak convergent validity in comparison with non-synchronous accelerometry [22].…”
Section: Assessment Of Leisure-time Physical Activitymentioning
confidence: 99%